Geopolitical Risk and Globalization - Thakkar, Nachiket; Ayub, Kiran Ambreen (Journal of Applied Business and Economics, 2022)
In this paper we examine the effect of geopolitical risks on globalization using Pseudo-Poisson Maximum Likelihood (PPML) methodology for gravity trade model. As a measure for globalization, we use bilateral foreign direct investment (FDI) data from 2001 to 2012 and bilateral trade data from 1948 to 2019. Ours is the first paper making use of the recently created geopolitical risk (GPR) dataset using text analysis to test its effect on globalization. For the univariate model, we find a significant decline in FDI by 3.6% and 0.5% in trade for 10% increase in geopolitical riskiness, but for multivariate model we only see a significant increase in trade by 0.04%. We test the robustness of our results by doing more granular analysis by using individual country GPR measures as well as using KOF Globalization Index instead of FDI and Trade flow. Here also we see a significant negative effect of geopolitical risk on globalization.